2023
DOI: 10.1186/s13256-023-03975-1
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation induced by gabapentin: a case report

Abstract: Background Gabapentin is commonly prescribed for the treatment of neuropathic pain, restless leg syndrome, and partial-onset seizures. Although the most frequent side effects of gabapentin are associated with the central nervous system, gabapentin can also affect the cardiovascular system. Case reports and observational studies have showed that gabapentin can be associated with increased risk of atrial fibrillation. However, all the evidence is concentrated in patients older than 65 years old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…There are no clinical studies to have investigated the side effects or toxicity of GBP on cardiovascular function, however, several case reports describe adverse cardiovascular events induced by GBP or its structurally similar compound, pregabalin. These include the development of new onset congestive heart failure [10,11], decompensation of pre-existing CHF [21][22][23], cardiac conduction disturbances [24,25], atrial fibrillation [9], and hypotension [13,26]. In an analysis of a large-scale nation-wide database of de-identified patients (TriNetZ EHRs), Pan et al [8] recently found a significant increase in the risk of cardiovascular diseases, including heart failure, myocardial infarction, peripheral vascular disease, stroke, deep venous thrombosis, and pulmonary embolism in patients with diabetic neuropathy following long-term use of GBP and pregabalin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no clinical studies to have investigated the side effects or toxicity of GBP on cardiovascular function, however, several case reports describe adverse cardiovascular events induced by GBP or its structurally similar compound, pregabalin. These include the development of new onset congestive heart failure [10,11], decompensation of pre-existing CHF [21][22][23], cardiac conduction disturbances [24,25], atrial fibrillation [9], and hypotension [13,26]. In an analysis of a large-scale nation-wide database of de-identified patients (TriNetZ EHRs), Pan et al [8] recently found a significant increase in the risk of cardiovascular diseases, including heart failure, myocardial infarction, peripheral vascular disease, stroke, deep venous thrombosis, and pulmonary embolism in patients with diabetic neuropathy following long-term use of GBP and pregabalin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a retrospective cohort study revealed a significantly increased risk of adverse cardiovascular events, including heart failure, myocardial infarction, peripheral vascular disease, stroke, deep venous thrombosis, and pulmonary embolism in patients with diabetic neuropathy following long-term use of GBP [8]. Furthermore, several clinical cases of GBP-induced atrial fibrillation [9], acute heart failure [10,11], cardiomyopathy [12], and intraoperative hypotension [13] have been reported recently. Thus, we postulate that these events may be attributed, in part, to the effects of GBP on Ca 2+ currents in cardiomyocytes or vascular smooth muscles.…”
Section: Introductionmentioning
confidence: 99%
“…There are no clinical studies to have investigated the side effects or toxicity of GBP on cardiovascular function, however, several case reports describe adverse cardiovascular events induced by GBP or its structurally similar compound, pregabalin. These include the development of new onset congestive heart failure [10,11], decompensation of pre-existing CHF [21][22][23], cardiac conduction disturbances [24,25], atrial fibrillation [9], and hypotension [13,26]. In an analysis of a large-scale nation-wide database of de-identified patients (TriNetZ EHRs), Pan et al [8] recently found a significant increase in the risk of cardiovascular diseases, including heart failure, myocardial infarction, peripheral vascular disease, stroke, deep venous thrombosis, and pulmonary embolism in patients with diabetic neuropathy following long-term use of GBP and pregabalin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a retrospective cohort study revealed a significantly increased risk of adverse cardiovascular events, including heart failure, myocardial infarction, peripheral vascular disease, stroke, deep venous thrombosis, and pulmonary embolism in patients with diabetic neuropathy following long-term use of GBP [8]. Furthermore, several clinical cases of GBP-induced atrial fibrillation [9], acute heart failure [10,11], cardiomyopathy [12], and intraoperative hypotension [13] have been reported recently. Thus, we postulate that these events may be attributed, in part, to the effects of GBP on Ca 2+ currents in cardiomyocytes or vascular smooth muscles.…”
Section: Introductionmentioning
confidence: 99%